Study of Security Problems in RFID Systems and Existing Solutions (International Journal of Scientific Research in Science and Technology, 2026)
In this present paper, we consider to measure the performance of an RFID system. On one hand, due to the countless number of tags in industries such as supply chain, the search overhead of a tag in the reader’s back-end database may be overwhelmingly high. Therefore, the search cost should be a concern. On the other hand, in order to protect an RFID system’s security, it is usually to implement an RFID protocol in the system. Thus, another cost of RFID security protocol is cryptographic operation cost as well as reader-tag communication cost. In [1-4], Avoine claimed that a cryptographic operation on a single computer only takes 2-23 second to finish, while it would take a lot more time to finish a cryptographic operation on a tag due to a tag’s limited memory and computational ability. Therefore, cryptographic operation cost in RFID reader side is ignorable.